(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In according to ISO 9000 the basis of quality management in accordance is the total production control using the systems of automated measurement of process values. Coordinated functioning of the water production links: pumping stations, pipelines, filtration equipment, etc. increases the efficiency and reliability of the hydrosystem, reduces energy consumption and improves organoleptic water performance. Modern water supply systems have a branched network structure, which is located on a vast territory. To monitor the parameters of the operation of technological equipment, a variety of sensors are intended, which convert the test value into an electrical signal entering the actuator. Effective approaches to controlling the functioning of electric motors of centrifugal pumps ensuring the transfer of required volumes of water are analyzed. In work algorithms of regulation of volume of water and pressure supply by pumping stations of city water service with application of innovative sensors are analyzed.